2014
DOI: 10.1088/1674-1056/23/11/115201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of some parameters on the divertor plasma sheath characteristics and fuel retention in castellated tungsten tile gaps

Abstract: Effects of some parameters on the divertor plasma sheath characteristics and fuel retention in castellated tungsten tile gaps * Sang Chao-Feng(桑超峰) a) † , Dai Shu-Yu(戴舒宇) a) , Sun Ji-Zhong(孙继忠) a) , Bonnin Xavier b) , Xu Qian(徐 倩) c) , Ding Fang(丁 芳) c) , and Wang De-Zhen(王德真) a) ‡

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The theory calculation based on the empirical potential was used to investigate the stable configuration, migration path of SIA and vacancies. [9][10][11] Previous studies and our calculations suggested that 111 -type SIA configurations have the lowest formation energy in all nonmagnetic bcc metals [12,13] and the energy difference with that of the 110 dumbbell is about 0.28 eV. However, the ferromagnetic bcc α-Fe is fundamentally different from other bcc metals.…”
Section: Introductionmentioning
confidence: 54%
“…The theory calculation based on the empirical potential was used to investigate the stable configuration, migration path of SIA and vacancies. [9][10][11] Previous studies and our calculations suggested that 111 -type SIA configurations have the lowest formation energy in all nonmagnetic bcc metals [12,13] and the energy difference with that of the 110 dumbbell is about 0.28 eV. However, the ferromagnetic bcc α-Fe is fundamentally different from other bcc metals.…”
Section: Introductionmentioning
confidence: 54%
“…[28] and [29]: the plasma core and edge region, the scrape-off-layer (SOL) region, and the private flux and divertor plate region. [30] In the simulations, the fueling source is injected to the low field side of the HL-2A tokamak.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Tungsten has been considered as one of the candidate PFMs for ITER because of its favorable physical and chemical properties, such as high thermal conductivity, high melting point, high-temperature mechanics performance, low physical and chemical sputtering yields, and no chemical reaction with hydrogen. [1][2][3][4][5][6][7] However, the brittleness of W material leads PFM to likely undergo crack failure when the transient event occurs. [8] W-Y 2 O 3 alloys can effectively impede the recovery and recrystallization at high temperature, and have low ductilebrittle transition temperature (DBTT) compared with pure tungsten.…”
Section: Introductionmentioning
confidence: 99%